The UV-LIDAR: A tool for investigating Aerosol-Cloud Interactions: A case study on Ascension Island - Tenner, Elma (author) (2017)
Climate change and human influences are widely investigated. However, the processes of aerosol-cloud interactions are still not adequately known and the associated lack of knowledge causes uncertainties in climate change prediction. Therefore this study presents different approaches to investigate those interactions, in particular the Twomey-effect, which states that an increase in aerosol loading leads to an increase in cloud drop number density and a decrease in cloud drop effective radius, considering constant liquid water path. The data analysed was obtained during the ASCII campaign 2016 at Ascension Island. Cloud and aerosol measurements were done by an ultra-violet (UV) lidar during the month September 2016. The cloud microphysical properties - cloud drop number density and cloud drop effective radius - were retrieved using the cloud property inversion retrieval algorithm. The cloud effective radius varied between 1.88 and 4.48 $μ m$. The cloud drop number density had values in the range of 228-1690 $cm^{-3}$. Furthermore, the total aerosol profiles for clear sky scenes and the aerosol profiles below clouds were retrieved, solving the boundary-value-problem using the ’Klett’ approach. For the aerosol profiles below clouds an extra factor was introduced, accounting for multiple scattering inside the clouds. The aerosol loading arrived at Ascension Island came mainly from the South (Atlantic Ocean) in the lower 1200m or from the East (African continent, biomass burning events) above 1200m. The aerosol-cloud interactions were examined for both the clear sky and the below cloud aerosols with the cloud properties. Both approaches gave evidence for the Twomey-effect. Those results suggest that the UV-lidar is a suitable instrument for investigation of aerosol-cloud interactions. Future projects can use those approaches to gain more knowledge over the interactions, enabling a major improvement of climate change predictions. Ascension Island Initiative 2016 (ASCII)